Digital Library Management Infor Digital Library Management Information System at Smk Tritech Informatika Medan - Irwan; Kartini, Siti Agus; Sabila, Puji Chairu (Bahasa Indonesia, 2023)
Information system is a system that combines human activities and the use of technology to support management and operational activities. A library is a place that contains a collection of books and other reading materials that are systematically arranged according to the rules so that they can used as a source of information. SMK Tritech Informatics Medan is one of the schools that have library facilities. In library management, it is generally not systemized or computerized, still doing data processing is still manual, by writing in ledgers related to information laying of reading books, writing library memberships, borrowing books and returning books and the difficulty of calculating late repatriation penalties. Another problem is also the difficulty of library employees finding member data and free libraries from each member. Based on this, it is hoped that later the existence of a digital library management information system can help librarians in solving problems and managing libraries well, easily and effectively at SMK Tritech Informatika Medan.